HUBUNGAN PERSEPSI KONSUMEN TERHADAP PRODUK OLEH OLEH KHAS BOGOR DENGAN PENGAMBILAN KEPUTUSAN PEMBELIAN - Novitasari Novitasari; Diana Amaliasari; Dwi Rini Sovia Firdaus (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
This study aims to determine the characteristics of consumers and consumer perceptions in making decisions about purchasing traditional food of Bogor, figure out the purchase decisions of traditional food of Bogor, find the correlation between characteristics and perceptions of consumers in decision-making of Bogor traditional food. Tourists who visited Bogor became the populations of this research. The samples are100 people using the Probability Sampling technique: Stratified random sampling. The results showed that the characteristics of consumers were dominated by women with an average age of 23-28 years, with Diploma / Bachelor education, with an average monthly income of Rp. 3,000,000-Rp. 4,000,000 and working as a private employee. Consumer perception in purchasing decisions of traditional food of Bogor showed the "upper" category because the average score obtained from the product quality indicator is 4.14, service quality is 3.85, prices is 3.88 and brands is 4.20 (scale 1 to 5). The decision to purchase a Bogor traditional food shows an average score with "agree” in category on each indicators about purchasing stability in a product of 3.98, the goal of buying a product of 3.81, information processing for up to purchase of 3.95, provide recommendations to others amounting to 3.46 (scale 1 to 5). There is no significant correlation between the characteristics of consumers with purchasing decision making with a correlation level of -0.024 (negative) means the the relationship between the two variables is opposing direction. The results of the analysis of the relationship between consumer perception variables with purchasing decision making showed a significant relationship with a correlation level of 0.360 (positive) with a high degree of correlation, so that the relationship between the two variables is unidirectional.Keywords: Consumer Perception, Consumer Behavior, Purchasing Decision Maker.